Primary standardization of 90Sr-90Y radioactive solution - KOSKINAS, MARINA F. (2018)
In the present work, the procedure developed by the Nuclear Metrology Laboratory (LMN) at IPEN, for the primary standardization of 90Sr-90Y, is presented. The method applied has been the efficiency tracing technique using a ??????????????? coincidence system. That consists in the measurement of a beta pure emitter along with a beta-gamma emitter, previously standardized, which will provide the beta efficiency. In this work, the beta-gamma emitter used was 60Co. The beta efficiency has varied using external absorbers, and the specific activity was determined using the extrapolation curve. ESQUEMA Code, which predicts the extrapolation curve by means of Monte Carlo technique, was applied, and the specific activity obtained from Monte Carlo simulation was compared with the experimental, showing good agreement within the experimental uncertainties.